Quercetin Suppresses Apoptosis and Attenuates Intervertebral Disc Degeneration via the SIRT1-Autophagy Pathway - Wang, Dong; He, Xin; Wang, Di; Peng, Pandi; Xu, Xiaolong; Gao, Bo; Zheng, Chao; Wang, Han; Jia, Haoruo; Shang, Qiliang; Sun, Zhen; Luo, Zhuojing; et al. (Frontiers in Cell and Developmental Biology, 2020)
Intervertebral disc degeneration (IDD) has been generally accepted as the major cause of low back pain (LBP), which causes an enormous socioeconomic burden. Previous studies demonstrated that the apoptosis of nucleus pulposus (NP) cells and the dyshomeostasis of extracellular matrix (ECM) contributed to the pathogenesis of IDD, and effective therapies were still lacking. Quercetin, a natural flavonoid possessing a specific effect of autophagy stimulation and SIRT1 activation, showed some protective effect on a series of degenerative diseases. Based on previous studies, we hypothesized that quercetin might have therapeutic effects on IDD by inhibiting the apoptosis of NP cells and dyshomeostasis of ECM via the SIRT1-autophagy pathway. In this study, we revealed that quercetin treatment inhibited the apoptosis of NP cells and ECM degeneration induced by oxidative stress. We also found that quercetin promoted the expression of SIRT1 and autophagy in NP cells in a dose-dependent manner. Autophagy inhibitor 3-methyladenine (3-MA) reversed the protective effect of quercetin on apoptosis and ECM degeneration. Moreover, SIRT1 enzymatic activity inhibitor EX-527, suppressed quercetin-induced autophagy and the protective effect on NP cells, indicating that quercetin protected NP cells against apoptosis and prevented ECM degeneration via SIRT1-autophagy pathway. In vivo, quercetin was also demonstrated to alleviate the progression of IDD in rats. Taken together, our results suggest that quercetin prevents IDD by promoting SIRT1-dependent autophagy, indicating one novel and effective therapeutic method for IDD.